2008
DOI: 10.1111/j.1469-7610.2008.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal psychotherapy with pregnant adolescents: two pilot studies

Abstract: IPT-PA appears feasible and helpful in managing and treating depression in pregnant girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Fourteen studies (52%) reported at least some information regarding the race, ethnicity, or national origin of subjects. In the 10 studies (37%) that reported demographic information that provided sufficient data regarding the racial composition of their samples, the percentage of subjects who identified as racial/ethnic minorities ranged from 0% (Klier et al, 2001) to 100% (Miller, Gur, Shanok, & Weissman, 2008), with a mean of 45.6% and standard deviation of 32.7%. Twenty-three studies (85%) reported information regarding the marital status of subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (52%) reported at least some information regarding the race, ethnicity, or national origin of subjects. In the 10 studies (37%) that reported demographic information that provided sufficient data regarding the racial composition of their samples, the percentage of subjects who identified as racial/ethnic minorities ranged from 0% (Klier et al, 2001) to 100% (Miller, Gur, Shanok, & Weissman, 2008), with a mean of 45.6% and standard deviation of 32.7%. Twenty-three studies (85%) reported information regarding the marital status of subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescent mothers report extreme stress from conflict with parents and/or romantic partners experienced in combination with financial hardship, societal expectations, cultural messages, and/or pubertal changes. 23,24 Adolescent women have also reported perceiving extreme stigma around psychiatric illness, particularly depression.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one published report of two small open-trial pilot studies (N=14 and N=11) addressed treatment for depression in pregnant adolescents 15 . Despite the potentially high burden of depression to young women and their families, studies on the prevention of postpartum depression in pregnant adolescents are virtually nonexistent.…”
Section: Introductionmentioning
confidence: 99%